Recent evolution on synthesis strategies and anti-leishmanial activity of β-carboline derivatives – An update. Issue 9 (September 2020) - Banoth, Karan Kumar; Faheem,; ChandraSekhar, Kondapalli Venkata Gowri; Adinarayana, Nandikolla; Murugesan, Sankaranarayanan
Abstract: Leishmaniasis is the most widespread pathogenic disease in several countries. Currently, no effective vaccines are available, and the control of Leishmaniasis primarily relies on decade-old chemotherapy. The treatment for the Leishmaniasis is not up to the mark. Current therapy for Leishmaniasis is ancient and requires hospitalization for the administration. These medications are also highly toxic and resistant. β-carboline, a natural indole containing alkaloid, holds a vital position in the field of medicinal chemistry with a diversified pharmacological action. The current review focuses mainly on the anti-leishmanial effects of β-carboline analogs and their synthetic strategies, structural activity relationship studies (SAR). The past ten years alterations unveiled by β-carboline analogs present in phytoconstituents and various derivatives of synthesized analogs with the mechanism of action were briefly shortlisted and illustrated. Abstract : Leishmaniasis; β-carboline; Synthesis; Amastigotes; Promastigotes; Phytoconstituents; Structure-activity relationship studies; Materials science; Chemistry; Natural product chemistry; Pharmaceutical chemistry; Biological sciences; Phytochemistry; Pharmaceutical science; Health sciences; Pharmacology